Drosophila Heterochromatin Stabilization Requires the Zinc-Finger Protein Small Ovary. Issue 3 (1st November 2019) - Benner, Leif; Castro, Elias A; Whitworth, Cale; Venken, Koen J T; Yang, Haiwang; Fang, Junnan; Oliver, Brian; Cook, Kevin R; Lerit, Dorothy A
Abstract: The small ovary ( sov ) locus was identified in a female sterile screen, yet its molecular identity and function remained a mystery for decades. In the present work, Benner et al. molecularly map... Heterochromatin-mediated repression is essential for controlling the expression of transposons and for coordinated cell type-specific gene regulation. The small ovary ( sov ) locus was identified in a screen for female-sterile mutations in Drosophila melanogaster, and mutants show dramatic ovarian morphogenesis defects. We show that the null sov phenotype is lethal and map the locus to the uncharacterized gene CG14438, which encodes a nuclear zinc-finger protein that colocalizes with the essential Heterochromatin Protein 1 (HP1a). We demonstrate Sov functions to repress inappropriate gene expression in the ovary, silence transposons, and suppress position-effect variegation in the eye, suggesting a central role in heterochromatin stabilization.